The Influence of US Presidential Tweets on Global Markets - Wu, Chen Y.; Pandey, Vivek K.; Lirely, Roger (Journal of Accounting and Finance, 2020)
Donald J. Trump is the first President of the United States to routinely use social media to comment on current events, political figures, celebrities and to make official policy announcements. We examine the effects of Trump’s tweets on subjects of interest to financial markets in the U.S. and abroad. We show that general comments about the US economy have very little impact on the market. Conversely, company-specific tweets tend to have a positive, but transient, impact. We find that Trump’s tweets escalating trade disputes tend to have a lasting negative impact on the equity markets of the concerned foreign nation.